ANALISIS PERILAKU PERKAWINAN USIA DINI DI KOTA MEDAN - Ridwan, Muhammad; Munir, Abdul (ANALITIKA, 2010)
When women entered the institution of marriage is believed to be perujudan ideal relationship between two individuals, then the sequence of work, giving birth, raising children, husbands and households are waiting, not to mention the problems will go through and deal with.This study is qualitative, based on phenomenological philosophy that prioritizes appreciation of the events of the interaction behavior analysis early marriage couples in certain circumstances be interpreted to understand the perspective of the researchers themselves. Given the results of this study is expected to make a contribution to the authorized officer, the parents, the early adolescents in this pase early teens, in order to think the most of the will to carry out an early marriage with the risks as the results in this study.